A review on biochar-mediated anaerobic digestion with enhanced methane recovery. (November 2019) - Qiu, L.; Deng, Y.F.; Wang, F.; Davaritouchaee, M.; Yao, Y.Q.
Abstract: This work comprehensively reviewed the research progress of biochar application in enhancing anaerobic digestion (AD) proficiency. The biogas production and methane content improvement, AD buffering capacity enhancement, and ammonia and VFAs inhibition alleviation were thoroughly discussed. AD is a technology for treating biowastes with energy recovery via microbial communities. However, this process has some limitations, which are particularly noticeable in the AD of biomass which is prone to ammonia or acid accumulation. At the high ammonia nitrogen concentrations, biochar addition can improve the tolerance of AD system within a specific range. Likewise, at the high organic loading rate (OLR), biochar could effectively delay the time up to VFAs accumulation threshold. At the microbial level, biochar has been used to support cell immobilization and microbial growth in AD system. The substantial specific surface area (SSA) and porous structure of biochar favor the colonization of syntrophic acetogenic bacteria and methanogenic archaea, which facilitate the total organic carbon removal as well as the reaction rate in AD. As an electron conductor, biochar addition can stimulate direct interspecies electron transfer (DIET) between syntrophic acetogen and methanogen communities in AD process. On the surface of biochar, the released electrons from exoelectrogenic microorganisms are directly transferred to electron-capturing microorganisms, instead of exoelectrogenic microorganisms. Microorganisms like Geobacter sp. and Shewanella sp, are known to be capable of transporting electrons through a chain of cytochrome c toward extracellular electron acceptors. Furthermore, the role of biochar as a carrier material on microbial growth, breeding, and metabolism were discussed. Also, the interspecies electron transfer (IET) mechanism involved in the AD process with biochar as an electron carrier was reviewed. Eventually, the policy-oriented recommendations and the research methods of life cycle assessment (LCA) on biochar-mediated AD are proposed, which can be considered as the reference for AD development. Graphical abstract: Image 1 Highlights: Biochar as an additive can promote methane production in AD system. Biochar improves the tolerance of microbes to high ammonia nitrogen content. Biochar enhances the buffering capacity of AD system related to VFAs. Biochar enhances microorganism metabolism and DIET mechanism in AD system. Perspectives for future research orientation on biochar application in AD were provided.